2014
DOI: 10.5539/res.v6n1p23
|View full text |Cite
|
Sign up to set email alerts
|

Housing Tenure Choice and Housing Expenditures in the Czech Republic

Abstract: Choosing between rented housing and homeownership, the so called housing tenure choice, is a key decision made by each household. Therefore housing economists often seek an answer to the question which factors have an impact on this decision. The paper investigates potential tenure choice determinants using probit regression model based on the sample data. Results of the analysis, making use of the investigation of EU-SILC in the CR, showed that tenure choice is affected by the factors similar to those in othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…This implies, as households are staying for long years, then households fulfill some of the criteria's to obtain land in the form of lease to construct, own house. This result is consistent with recent studies conducted in the Czech Republic which indicated that years of residence was significant variable in explaining housing choice (Spalkoval and Jiri Spalik, 2014).…”
Section: Years Of Residence (Yred)supporting
confidence: 93%
See 1 more Smart Citation
“…This implies, as households are staying for long years, then households fulfill some of the criteria's to obtain land in the form of lease to construct, own house. This result is consistent with recent studies conducted in the Czech Republic which indicated that years of residence was significant variable in explaining housing choice (Spalkoval and Jiri Spalik, 2014).…”
Section: Years Of Residence (Yred)supporting
confidence: 93%
“…In addition, peoples' preference was more focused on the double and single level of building houses. Spalkoval and Jiri (2014) conducted on housing tenure choice and housing expenditures in the Czech Republic. The paper investigates potential tenure choice determinants using probit regression model based on the sample data.…”
Section: Over View Of the Literaturementioning
confidence: 99%
“…The housing tenure statuses by households (renting or owner-occupancy) are influenced by a multitude of factors, some of which cannot be directly measured [1]. Though it is neither possible nor practical to measure and include all the explanatory variables that influence housing tenure and affordability, economists are still interested in studying the patterns and levels of influence of any available measurable explanatory variables (for example [2][3][4][5]).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, some studies have opted to use other binary link functions such as the logit function, which assumes a more flexible logistic distribution. However, the methods used in these studies do not allow for joint modeling, where dependence is assumed to exist between the binary responses [4,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…One of the key decisions made by any household is the choice between owning and renting their home (Dagmar et al;2014). According to Arimah (1997), a key factor in tenure choice decision is the relative price of home-owning to that of renting.…”
Section: Introductionmentioning
confidence: 99%